2011
DOI: 10.1371/journal.pone.0022987
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exposure to Severely Limited Sleep Results in Distinctive and Persistent Physiological Imbalances in Rats

Abstract: Chronic sleep disruption in laboratory rats leads to increased energy expenditure, connective tissue abnormalities, and increased weights of major organs relative to body weight. Here we report on expanded findings and the extent to which abnormalities become long-lasting, potentially permanent changes to health status after apparent recuperation from chronic sleep disruption. Rats were exposed 6 times to long periods of disrupted sleep or control conditions during 10 weeks to produce adaptations and then were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 123 publications
(169 reference statements)
3
34
0
2
Order By: Relevance
“…These critical questions emphasize the need for future prolonged naturalistic field studies in humans. Notably, recent experiments in animals showed that repeated sleep restriction/ recovery cycles resulted in energy deficiency as shown by hyperphagia and significant weight loss and decreased plasma corticosterone and leptin concentrations as a consequence of diminished adiposity (12,13). Some of these changes were still present even after a 4-mo-long recuperation period, suggesting that repeated sleep restriction/recovery cycles may have lasting effects, which in turn may increase the likelihood of various diseases (13).…”
Section: Discussionmentioning
confidence: 99%
“…These critical questions emphasize the need for future prolonged naturalistic field studies in humans. Notably, recent experiments in animals showed that repeated sleep restriction/ recovery cycles resulted in energy deficiency as shown by hyperphagia and significant weight loss and decreased plasma corticosterone and leptin concentrations as a consequence of diminished adiposity (12,13). Some of these changes were still present even after a 4-mo-long recuperation period, suggesting that repeated sleep restriction/recovery cycles may have lasting effects, which in turn may increase the likelihood of various diseases (13).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, insufficient sleep per se may not directly lead to weight gain and findings from nonhuman models support the latter. Specifically, sleep-restricted rodents lost weight even though they ate more (24) and rats with sleep disturbance because of ventrolateral preoptic area of the hypothalamus lesions (25) gained less weight even though they ate normal amounts of food. Although EE was not directly measured in the latter rodent studies, the findings are consistent with the physiological principal that energy needs are higher during sleep loss.…”
Section: Energy Expenditure and Energy Intake During Sleep Loss Andmentioning
confidence: 99%
“…In a study spanning 72 d, rats underwent six cycles of 10 d sleep fragmentation by platform rotation followed by two days of recovery. The decrease of leptin was not significantly different even though there was weight loss [42]. …”
Section: Lack Of Effect Of Sleep Fragmentation On Leptin In Both Humamentioning
confidence: 99%